Variation in Community Structure and Abundance of Fish in Simple Structured Shallow Sandy Habitats - Veneranta, Lari; Westerbom, Mats (Wiley-Blackwell, 2024)
Sandy beaches and their surf zones characterise many of the world's open coastlines. They are important breeding, nursery and feeding areas for many species of fish. Despite the commonness and importance of sandy beach surf zones, the dynamics, space occupancy and diversity patterns of residing fish is in many places poorly understood. The aim of this study was to (1) characterise the fish community structure in 11 simple structured sandy surf zones of the northern Baltic Sea and (2) relate variation in fish abundance and community structure to a set of chosen abiotic variables. Using beach seine, weekly or biweekly sampling was conducted at fixed sites at 10 occasions throughout a summer season. A total of 60,006 fish individuals belonging to 20 species were recorded. Changes in abundance and community structure were mainly driven by the variation of only five species reflecting species-specific recruitment patterns and different spatial responses to abiotic variables. Dominating groups were Gasterosteidae, Ammodytidae and Gobiidae that together formed 86% of the total adult fish catches. Larval numbers were completely dominated by Gobiidae. Multivariate analyses indicated species-specific responses to measured environmental variables, most important being a combination of wave exposure, beach slope, bottom roughness, and temperature. The present study shows that changes in fish abundance on simple structured sandy sublittoral beaches in the northern Baltic Sea are large over the course of a breeding season. It also reveals that variation in adult and juvenile fish are driven by a set of abiotic factors that influence on the fish assemblage structure through mainly species-specific, rather than through generic responses. Unravelling the degree to which the sandy shore fish community vary in the northern Baltic Sea will help in managing coastal environments that are increasingly being threatened by many anthropogenic stressors.
Keywords: Itämeri; nuottakalastus; Kalayhteisö; hiekkaranta